Perancangan Klasifikasi Pemetaan Kelas Siswa Unggulan Menggunakan Metode K-Means Clustering Pada SMA Negeri 3 Tanjung Balai Berbasis Web - Hafiz, Muhammad Farhan; Faisal, Ilham; Lubis, Imran (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2022)
SMA Negeri 3 Tanjung Balai currently does not have a system that can classify students with high average scores, because previously the school grouped students into superior classes by checking the grades of the students one by one in a manual way with the number of large student data, therefore a system is needed in order to be able to classify students into superior classes based on existing criteria at the school such as student report scores, extracurricular, discipline, achievement and student creativity in a very easy way, without having to look at student data one by one . The process of designing this application uses the PHP programming language and database, with this system the school only inputs student scores into the system, and automatically the system will classify which students will enter the superior class, and the ordinary class. By using the k-means clustering algorithm and applied with a database technology called data mining, the clustering algorithm is one of the data mining techniques which in the process tries to partition existing data into clusters and data mining itself is a technology used to determine different data to support decision making, data that have the same in the same group and which will be grouped into other groups. Keywords: K-means clustering, Data mining, SMA Negeri 3 Tanjung Balai